2014
DOI: 10.5604/15093492.1135122
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Patients with Degenerative Disease of the Spine and Their Guality of Life.

Abstract: STRESZCZENIEWstęp. Ce lem ba dań by ło po zna nie pro ble mów zdro wot nych pa cjen tów z cho ro bą zwy rod nie nio wą krę go słu -pa (głów ną przy czy ną ob ni że nia spraw no ści fi zycz nej) oraz okre śle nie za po trze bo wa nie na edu ka cję zdro wot ną.Ma te riał i me to dy. Ba da niem ob ję to 50 osób. Wy ko rzy sta no me to dę son da żu dia gno stycz ne go przy uży -ciu au tor skie go kwe stio na riu sza an kie ty. Na rzę dziem ba daw czym prze zna czo nym do oce ny ja ko ści ży cia by ła an kie ta WHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The average GHS score for our CLBP patients was significantly lower than the average OQOL score, as was similarly reported in Polish patients. 41 More so, dissatisfaction with general health was common (more than two-thirds of our patients), while less than a tenth rated their QoL as poor. In an Austrian study, 20 though a similar disparity was observed between the two scores, health dissatisfaction was less common (about a quarter of their patients) than in our cohort.…”
Section: Discussionmentioning
confidence: 66%
“…The average GHS score for our CLBP patients was significantly lower than the average OQOL score, as was similarly reported in Polish patients. 41 More so, dissatisfaction with general health was common (more than two-thirds of our patients), while less than a tenth rated their QoL as poor. In an Austrian study, 20 though a similar disparity was observed between the two scores, health dissatisfaction was less common (about a quarter of their patients) than in our cohort.…”
Section: Discussionmentioning
confidence: 66%
“…According to a study by Talaga et al, In a study involving 50 subjects, the aim was to investigate health problems in patients with degenerative spinal diseases as a major cause for worsening physical fitness and to determine the need for health education. Researchers have come to the conclusion that major health problems were cervical and lumbar pain in the spine that was experienced during prolonged physical activity during everyday life, quality of life decreased with increasing difficulties in performing daily activities, it is important to strengthen the patient’s belief that physical activity, including and physiotherapy, has a positive influence on physical ability and ability to perform daily activities, and the essential goal of the therapeutic team is to support and motivate patients to struggle with difficult situations and function in society ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in walking ability can result from these spinal dysfunctions in combination or alone. Talaga et al [6] reported that 56 % of patients with degenerative spinal disorders have experienced difficulty in performing social activities and had psychological problems, such as a sense of inferiority (54 %) and feeling lonely (24 %). Thus, degenerative spinal disorders can affect not only ADL but also social participation of the elderly.…”
Section: Introductionmentioning
confidence: 98%